Clinical auditing as an instrument to improve care for patients with ovarian cancer: The Dutch Gynecological Oncology Audit (DGOA). Issue 7 (July 2021) - Baldewpersad Tewarie, N.M.S; van Driel, W.J.; van Ham, M.; Wouters, M.W.; Kruitwagen, R.; Baalbergen, A.; Cate, A.D. Ten; Aalders, A.L.; van der Kolk, A.; Kruse, A.J.; Van Haaften-de Jong, A.M.L.D.; et al.
Abstract: Introduction: The Dutch Gynecological Oncology Audit (DGOA) was initiated in 2014 to serve as a nationwide audit, which registers the four most prevalent gynecological malignancies. This study presents the first results of clinical auditing for ovarian cancer in the Netherlands. Methods: The Dutch Gynecological Oncology Audit is facilitated by the Dutch Institute of Clinical Auditing (DICA) and run by a scientific committee. Items are collected through a web-based registration based on a set of predefined quality indicators. Results of quality indicators are shown, and benchmarked information is given back to the user. Data verification was done in 2016. Results: Between January 01, 2014 and December 31, 2018, 6535 patients with ovarian cancer were registered. The case ascertainment was 98.3% in 2016. The number of patients with ovarian cancer who start therapy within 28 days decreased over time from 68.7% in 2014 to 62.7% in 2018 (p < 0.001). The percentage of patients with primary cytoreductive surgery decreased over time (57.8%–39.7%, P < 0.001). However, patients with complete primary cytoreductive surgery improved over time (53.5%–69.1%, P < 0.001). Other quality indicators did not significantly change over time. Conclusion: The Dutch Gynecological Oncology Audit provides valuable data on the quality of care on patients with ovarian cancer in the Netherlands. Data show variation between hospitals with regard to pre-determined quality indicators. Results of 'best practices' will be shared with all participants of the clinical audit with the aim of improving quality of care nationwide. Highlights: The Dutch Gynecological Oncology Audit is a population-based data base that aims to improve quality of care. Over the years, patients with ovarian cancer underwent more complete primary cytoreductive surgery. Future results from the DGOA can be useful in identifying best practices and outliers.